Design of an Efficient Traffic Control Signal Using Webster’s Model: A Case Study of Akure, Nigeria - Reuben Ayodeji Bolaji; Olumuyiwa Samson Aderinola; Moses Ariyo Oladipo; Temitope Elizabeth Oguntelure; Michael Oluwagbenga Abanire (Disaster in Civil Engineering and Architecture, 2026)
The fast growth of cities and the increase in automobile usage have made important junctions more congested. This study employs the Webster model to design an efficient traffic signal for Araromi intersection in Akure, Nigeria, using the site traffic data. Results of field observations showed that passenger cars formed the dominant vehicle category, while the observed peak hour (7:45-8:45 AM) recorded a passenger car unit (PCU) of 6505 and a peak flow rate of 6920 pcu/hr. The critical flow ratio of 0.736 confirms that the intersection remains within capacity and the geometry is sufficient. The peak hour factor of 0.94 also indicates that a reliable and efficient signal control system can be effectively implemented at the intersection. The west approach contributed 41% of the total traffic, justifying its longer green interval, followed by the east (35%) and north (24%) approaches. The optimized signal design resulted in a cycle length of 110 seconds. Within this cycle, phases 1, 2, and 3 received 35, 32, and 28 seconds of effective green time, respectively, along with 4 seconds yellow interval for each phase. The signal achieved Level of Service (LOS) C on all approaches, with control delays of 29.94, 31.95, and 32.55 secs/veh, and a volume-to-capacity ratio below 1, indicating stable operations within capacity. This validates the efficiency of the Webster-based signal design and possible improvements in the performance of the intersection when implemented in pretimed or vehicle actuated traffic control systems. These findings provide a practical template for similar urban intersections in the implementation of efficient traffic signals.